2013
DOI: 10.3349/ymj.2013.54.6.1438
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated Contrast Media Can Induce Long-Lasting Oxidative Stress in Hemodialysis Patients

Abstract: PurposeDue to their comorbidities, dialysis patients have many chances to undergo radiologic procedures using iodinated contrast media. We aimed to assess time-sequenced blood oxidative stress level after contrast exposure in hemodialysis (HD) patients compared to those in the non-dialysis population.Materials and MethodsWe included 21 anuric HD patients [HD-coronary angiography (CAG) group] and 23 persons with normal renal function (nonHD-CAG group) scheduled for CAG, and assessed 4 oxidative stress markers [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Iodixanol induces disorders in five metabolic pathways related to oxidative stress, including glutamine and glutamate metabolism; alanine, aspartate and glutamate metabolism; glycine, serine and threonine metabolism; glutathione metabolism; taurine and hypotaurine metabolism. Previous work reported that prolonged and severe oxidative stress was observed in hemodialysis patients with CM injections [ 22 ]. In this study, we found that several antioxidative molecules (glutathione, creatine, and fumarate) were decreased in iodixanol-treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Iodixanol induces disorders in five metabolic pathways related to oxidative stress, including glutamine and glutamate metabolism; alanine, aspartate and glutamate metabolism; glycine, serine and threonine metabolism; glutathione metabolism; taurine and hypotaurine metabolism. Previous work reported that prolonged and severe oxidative stress was observed in hemodialysis patients with CM injections [ 22 ]. In this study, we found that several antioxidative molecules (glutathione, creatine, and fumarate) were decreased in iodixanol-treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed that iodinated radiographic contrast media caused severe and prolonged oxidative stress in hemodialysis patients. Moreover, iodinated radiographic contrast media increased advanced oxidation protein products (AOPP), catalase, 8-hydroxydeoxyguanosine, and malondialdehyde, which are oxidative stress markers, in hemodialysis patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%